Neurosustainability - Khalil, Mohamed Hesham (Frontiers in Human Neuroscience, 2024)
The human brain is in a constant state of change, evolving to dominate nature with increasing sophistication. However, this evolution has introduced a paradox: while the modern environment contributes to the de-evolution of the human brain, it also contains the antidote for its neuroplasticity. This paper introduces Neurosustainability as a novel paradigm that addresses the static state of contemporary living and its impact on the brain's neuroplasticity. It calls for a paradigm shift to move beyond the contemporary by going back to nature without having to go back in time where epigenetics mediates the neuroplastic processes and promises Neurosustainability as a long-term trait. Through an innovative neuro-evidenced framework comprising four enrichment scopes-spatial, natural, aesthetic, and social complexities holding multifaceted, interrelated attributes embedded in nature-we can harness the quintessential essence of nature to sustain and enhance the neuroplasticity of the human brain. Neurosustainability advocates integrating these multifaceted natural attributes into architecture and urban design, viewing them as independent variables that continuously architect the human brain. This approach aims to foster cognitive health and psychological resilience, addressing the pervasive issues of depression, anxiety, stress, and cognitive decline, thereby offering a pathway to more lifelong sustainable human brain health.